Escherichia coli β-Lactamases: What Really Matters - Bajaj, Priyanka; Singh, Nambram S.; Virdi, Jugsharan S. (Frontiers in Microbiology, 2016)
Escherichia coli strains belonging to diverse pathotypes have increasingly been recognized as a major public health concern. The β-lactam antibiotics have been used successfully to treat infections caused by pathogenic E. coli. However, currently, the utility of β-lactams is being challenged severely by a large number of hydrolytic enzymes – the β-lactamases expressed by bacteria. The menace is further compounded by the highly flexible genome of E. coli, and propensity of resistance dissemination through horizontal gene transfer and clonal spread. Successful management of infections caused by such resistant strains requires an understanding of the diversity of β-lactamases, their unambiguous detection, and molecular mechanisms underlying their expression and spread with regard to the most relevant information about individual bacterial species. Thus, this review comprises first such effort in this direction for E. coli, a bacterial species known to be associated with production of diverse classes of β-lactamases. The review also highlights the role of commensal E. coli as a potential but under-estimated reservoir of β-lactamases-encoding genes.